Investigation of Weight Fraction and Alkaline Treatment on Catechu Linnaeus/Hibiscus cannabinus/Sansevieria Ehrenbergii Plant Fibers-Reinforced Epoxy Hybrid Composites - R. Rangaraj; S. Sathish; T. L. D. Mansadevi; R. Supriya; Raviteja Surakasi; M. Aravindh; Alagar Karthick; V. Mohanavel; M. Ravichandran; M. Muhibbullah; Sameh M. Osman (Advances in Materials Science and Engineering)
The aim of the present work is to develop novel hybrid composites using areca, kenaf, and snake grass fibers as reinforcement and epoxy as the matrix. The areca, kenaf, and snake grass fibers were extracted from Catechu Linnaeus, Hibiscus cannabinus, and Sansevieria Ehrenbergii plants, respectively, and treated with 5% NaOH to improve the interfacial adhesion between the hydrophilic fiber and the hydrophobic matrix. Hybrid composites were developed by the compression molding technique and formulated based on the weight fraction of fibers. Tensile, flexural, and impact strength and hardness samples were prepared as per ASTM D 3039, ASTM D 790, ASTM D 256, and ASTM D 2240, respectively. The effects of alkaline treatment on developed hybrid composites were investigated. The developed hybrid composites with 20% wt. snake grass and 10% wt. areca fiber present interesting mechanical properties with a tensile strength of 58 MPa, flexural strength of 124 MPa, impact strength of 5.24 kJ/m2, and hardness of 88. The results indicate that maximum mechanical properties were obtained for alkaline-treated fiber composites with 20% wt. snake grass fiber compared to untreated fiber composites owing to better adhesion between the treated fiber and the matrix. The effect of alkaline treatment was analyzed by Fourier transform infrared. The fractured surfaces of tested samples were analyzed by scanning electron microscopy.